2016
DOI: 10.1007/s00125-016-4052-y
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine- and amphetamine-regulated transcript: a novel regulator of energy homeostasis expressed in a subpopulation of pancreatic islet cells

Abstract: Type 2 diabetes is characterised by chronic hyperglycaemia and its incidence is highly increased by exaggerated food consumption. It results from a lack of insulin action/production, but growing evidence suggests that it might also involve hyperglucagonaemia and impaired control of glucose homeostasis by the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Both CART precursors have been reported to be abundantly expressed in brain, pituitary and also in other peripheral tissues such as eye, interrenal tissues, and gonads in goldfish (39). CART exerts multiple physiological functions in fish, including the inhibition of appetite (39), regulation of the stress response (40) and energy balance (41).…”
Section: Hormones Regulating Food Intakementioning
confidence: 99%
“…Both CART precursors have been reported to be abundantly expressed in brain, pituitary and also in other peripheral tissues such as eye, interrenal tissues, and gonads in goldfish (39). CART exerts multiple physiological functions in fish, including the inhibition of appetite (39), regulation of the stress response (40) and energy balance (41).…”
Section: Hormones Regulating Food Intakementioning
confidence: 99%
“…In the pancreas, CART serves a physiological role in regulating both endocrine and exocrine pancreatic secretions (20). CART also regulates islet hormone secretion (21) and gastrointestinal tract motility (22). A previous study demonstrated that CART is positively associated with oxidative stress (23).…”
Section: Introductionmentioning
confidence: 99%
“…They decrease food intake and increase energy expenditure [3]. CART is widely expressed in the CNS, including brain regions controlling food intake, and direct administration of CART decreases food intake [4]. CART is believed to increase metabolism by causing an increase in the release of thyrotropin-releasing hormone (TRH) that in turn A. Webber-Waugh et al Journal of Behavioral and Brain Science stimulates release of thyroid stimulating hormone to cause an increase in heat production by muscle and adipose tissue [5].…”
Section: Introductionmentioning
confidence: 99%